Malignant Phyllodes Tumor of the Breast With Metastasis to the Orbit: A Rare Case Report. Issue 1 (January 2021) - Vempuluru, Vijitha S; Mishra, Dilip K; Kaliki, Swathi
Abstract : Phyllodes tumors are rare and account for 0.5% of all mammary neoplasms. They commonly present as lobulated breast tumors and have a variable clinical course. Histologically, phyllodes tumor is composed of 2 major elements: stromal element composed of spindle cells admixed with collagen and epithelial element in the form of epithelium lined cysts and clefts. Metastasis is rarely seen with phyllodes tumors. Sarcomatous component of phyllodes tumor metastasizes to lung, liver, adrenal, brain, and bones by hematogenous route. A thorough literature search did not reveal any report of orbital metastasis from malignant phyllodes tumor. Here, the authors describe a rare case of malignant phyllodes tumor of the breast with metastasis to the orbit in a 46-year-old female patient. Abstract : Orbital metastasis from phyllodes tumor is rare and histopathological diagnosis can be a challenge owing to the change in tumor morphology which mandates a high index of suspicion and judicious immunohistochemical profiling.